2002
DOI: 10.1097/01.lab.0000018917.69993.ba
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes-Prone NZO/Hl Strain. II. Pancreatic Immunopathology

Abstract: SUMMARY:We report the first combined light and electron microscopic analysis of the pancreas during the development of type 2 diabetes in the New Zealand Obese (NZO) mouse. As in most other polygenic rodent models of type 2 diabetes, hyperglycemia associated with beta cell destruction is male sex-limited. Increasing degrees of hyperinsulinemia and transition to diabetes were clearly reflected by the islet volume fraction, by the beta cell granulation state, and by ultrastructural changes, primarily of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…We also observed a higher proportion of B-1 B lymphocytes in peritoneal lavages from 8-month-old NZO than from NZB mice with concomitant high titers of IgM in the serum (data not shown). In the accompanying article (Junger et al, 2002), the presence of plasma cells in diabetic NZO islet perivascular infiltrates strengthens the hypothesis that these plasma cells could be B-1 cells that have migrated from peritoneal exudate cells after nonspecific activation, saw islet antigen in pancreatic lymph nodes, and differentiated into autoantibody producing cells. A high but variable number of resident peritoneal cells in NZO mice, resulting primarily from expansion of the B lymphocyte population, and including B-1 B lymphocytes, was not specifically associated with diabetes in NZO males.…”
Section: Discussionmentioning
confidence: 64%
“…We also observed a higher proportion of B-1 B lymphocytes in peritoneal lavages from 8-month-old NZO than from NZB mice with concomitant high titers of IgM in the serum (data not shown). In the accompanying article (Junger et al, 2002), the presence of plasma cells in diabetic NZO islet perivascular infiltrates strengthens the hypothesis that these plasma cells could be B-1 cells that have migrated from peritoneal exudate cells after nonspecific activation, saw islet antigen in pancreatic lymph nodes, and differentiated into autoantibody producing cells. A high but variable number of resident peritoneal cells in NZO mice, resulting primarily from expansion of the B lymphocyte population, and including B-1 B lymphocytes, was not specifically associated with diabetes in NZO males.…”
Section: Discussionmentioning
confidence: 64%
“…An earlier study reported that pancreatic islets of diabetic NZO mice are infiltrated by leucocytes [13], suggesting a role of the immune system in beta cell damage in NZO. In the present study, we observed infiltration of islets at a later stage of beta cell destruction, when cells had become necrotic.…”
Section: Discussionmentioning
confidence: 95%
“…The NZO mouse is an optimal model for the study of obesityassociated diabetes ('diabesity'). It presents morbid obesity associated with hyperphagia and reduced energy expenditure [9], rapidly developing a form of diabetes that is characterised by marked hyperglycaemia and hypoinsulinaemia associated with beta cell destruction [10][11][12][13]. Exposure to a 'cafeteria-type' high-fat diet (HFD) accelerated that process, apparently supporting the concept of lipotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ER size is considered an early adaptive response to ER stress [14][15][16]39]. This feature has been observed in beta cells during the development of type 2 diabetes in the New Zealand Obese mouse [40], and, more recently, also in beta cells of the Akita mouse, a monogenic diabetes model caused by a missense mutation of the insulin 2 gene [21], which leads to accumulation of mutant proinsulin and severe ER stress. In the Akita mouse beta cells, the volume density of ER was increased by 1.7-fold [41], which is similar to our findings in human diabetic beta cells.…”
Section: Discussionmentioning
confidence: 99%